The Use of 68Ga-DOTATATE PET/CT in the Non-invasive Diagnosis of Optic Nerve Sheath Meningioma: A Case Report - Al Feghali, Karine A.; Yeboa, Debra N.; Chasen, Beth; Gule, Maria K.; Johnson, Jason M.; Chung, Caroline (Frontiers in Oncology, 2018)
We hereby report the case of a patient with optic nerve sheath meningioma (ONSM), whose diagnosis and multidisciplinary management was guided by the use of Gallium-68 (68Ga)-labeled dodecanetetraacetic acid-tyrosine-3-octreotate (DOTATATE) positron emission tomograpgy (PET)/computed tomography (CT) scan. We briefly review the diagnosis and management of ONSM, and review the literature on the role and current status of nuclear imaging with somatostatin receptor ligands in the non-invasive diagnosis and management of meningiomas.